Analysis of Multiple Positive Feedback Paradigms Demonstrates a Complete Absence of LH Surges and GnRH Activation in Mice Lacking Kisspeptin Signaling - Dror, Tal (Society for the Study of Reproduction, Inc., 2013)
Kisspeptin stimulates gonadotropin-releasing hormone (GnRH) neurons via the kisspeptin receptor, Kiss1r. In rodents, estrogen-responsive kisspeptin neurons in the rostral hypothalamus have been postulated to mediate estrogen-induced positive feedback induction of the preovulatory luteinizing hormone (LH) surge. However, conflicting evidence exists regarding the ability of mice lacking Kiss1r to display LH surges in response to exogenous hormones. Whether the discrepancy reflects different mouse strains used and/or utilization of different surge-induction paradigms is unknown. Here, we tested multiple hormonal paradigms in one Kiss1r knockout (KO) model to see which paradigms, if any, could generate circadian-timed LH surges. Kiss1r KO and wild-type (WT) females were ovariectomized, given sex steroids in various modes, and assessed several days later for LH levels in the morning or evening (when surges occur). Serum LH levels were very low in all morning animals, regardless of genotype or hormonal paradigm. In each paradigm, virtually all WT females displayed clear LH surges in the evening, whereas none of the KO females demonstrated LH surges. The lack of LH surges in KO mice reflects a lack of GnRH secretion rather than diminished pituitary responsiveness from a lifetime lack of GnRH exposure because KO mice responded to GnRH priming with robust LH secretion. Moreover, high cfos-GnRH coexpression was detected in WT females in the evening, whereas low cfos-GnRH coexpression was present in KO females at all time points. Our findings conclusively demonstrate that WT females consistently display LH surges under multiple hormonal paradigms, whereas Kiss1r KO mice do not, indicating that kisspeptin-Kiss1r signaling is mandatory for GnRH/LH surge induction.